Drug reaction with eosinophilia and systemic symptoms syndrome associated with Nitrofurantoin - Jitendra Singh; Anju Dinkar; Virendra Atam; Kamlesh K Gupta; Krishna Kumar Sahani (Wolters Kluwer Medknow Publications, 2016)
Drug reaction with eosinophilia and systemic symptom (DRESS) is a severe adverse drug-induced reaction with a prolonged latency period which is characterized by a variety of clinical manifestations, usually fever, rash, lymphadenopathy, eosinophilia, and a wide range of mild-to-severe systemic presentations. Drugs are an important cause of DRESS in most of the cases. It is challenging to diagnose DRESS because of the diversity of cutaneous eruption and visceral organs involvement. We hereby report a 34-year-old female who developed DRESS syndrome following ingestion of nitrofurantoin for the treatment of urinary tract infection. She was managed conservatively and recovered after few weeks. Our aim of this study is to raise awareness to suspect DRESS syndrome in patients who present with unusual clinical features with skin involvement after initiating any drug.